Particle radiotherapy for breast cancer - Ruan, Hanguang; Okamoto, Masahiko; Ohno, Tatsuya; Li, Yang; Zhou, Yuan (Frontiers in Oncology, 2023)
Breast cancer is the most common malignant tumor in female patients. Along with surgery, radiotherapy is one of the most commonly prescribed treatments for breast cancer. Over the past few decades, breast cancer radiotherapy technology has significantly improved. Nevertheless, related posttherapy complications should not be overlooked. Common complications include dose-related coronary toxicity, radiation pneumonia, and the risk of second primary cancer of the contralateral breast. Particle radiotherapy with protons or carbon ions is widely attracting interest as a potential competitor to conventional photon radiotherapy because of its superior physical and biological characteristics. This article summarizes the results of clinical research on proton and carbon-ion radiotherapy for treating breast cancer.